The Influence of Social Networking Sites in the Political Participation of College Students: A Cognitive and Communication Mediation Model Analysis - Rabaca, Cyrene Faith D.; Butalid, May Alinie (Jurnal Studi Pemerintahan, 2025)
Scholars are optimistic that social media can enhance the democratic engagement of young adults. This research sought to identify social networking sites' direct and indirect influence (Facebook, Twitter, and TikTok) on students' political participation at San Isidro College through a cognitive communication mediation model analysis. There were three hundred thirty-five respondents through a simple random sampling method. Students' political participation differs based on their motivations for using social networking sites, where social utility ranks first, followed by entertainment, surveillance, and guidance. The study revealed that only social utility motivations have a highly significant direct influence on online political participation. It means that respondents' motivation to use social networking sites to communicate with others directly influences online political participation. Furthermore, guidance and surveillance motivation significantly and indirectly influence online and offline political participation, mainly through news consumption, political expression, political knowledge, and political efficacy. The findings suggest that the desire to know about the opinion of others (guidance) and to find the information they are interested in (surveillance) on social networking sites was significantly influenced by their SNS news consumption, SNS expression, political knowledge, and political efficacy, leading them to participate politically both online and offline. On the other hand, entertainment motivation does not predict political participation.